The Role Of The Family In Supporting The Recovery Of Female Prisoners In Prison Institutions - Mitro Subroto; Fahreza Alif Ramadhan (Universitas Merdeka Madiun, 2025)
Abstract Introduction to the Problem: Women prisoners often experience high levels of stress and stigma, which can hinder their rehabilitation and reintegration into society. One crucial yet often overlooked factor in their recovery process is the role of family support. Emotional and practical assistance from family members can significantly impact their mental well-being and overall rehabilitation journey. However, the extent and effectiveness of this support within correctional institutions remain underexplored. Purpose/Study Objectives: This research aims to analyze the role of family support in aiding the recovery of incarcerated women. Specifically, it seeks to examine how emotional, financial, and educational support from family members contributes to the rehabilitation process. Additionally, the study explores the need for family training programs to enhance their ability to assist in the reintegration process. Design/Methodology/Approach:A qualitative research approach was employed to gain an in-depth understanding of the dynamics of family support for incarcerated women. The study utilized in-depth interviews with women prisoners and their family members to gather firsthand insights into the nature and impact of familial assistance. The qualitative methodology allowed for a comprehensive exploration of emotional, financial, and educational support mechanisms within the correctional setting. Findings:The research findings indicate that family support plays a crucial role in the rehabilitation of women prisoners. Emotional support from family members helps alleviate stress and provides motivation for inmates to engage in rehabilitation programs. Financial support enables access to better healthcare and personal necessities, improving their well-being during incarceration. Furthermore, active family involvement in educational and skills training programs enhances the chances of successful reintegration into society post-release. The study also highlights the need for structured family training programs to equip relatives with the necessary knowledge and skills to support rehabilitation effectively. These findings underscore the importance of correctional institutions incorporating family-inclusive rehabilitation strategies to foster a more supportive environment for women prisoners. Paper Type: Research Article